Shifting the Burden of Corporate Taxes – Heterogeneity in Direct Wage Incidence - Nils aus dem Moore (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We contribute to the empirical literature on the effective incidence of corporate income taxation. We focus on the so-called direct incidence via the wage bargaining process. Building on the innovative framework of Arulampalam, Devereux and Maffini (2012), we analyze the importance of various dimensions of heterogeneity at the firm-level. In particular, we investigate the distinct effects of (i) firm size, (ii) level of profitability, and (iii) competition intensity across (iv) different economic sectors. Furthermore, we investigate the relative importance of the surrounding institutional setting. To this end, a firm-level within-country approach is pursued separately for two different economies, namely France and the United Kingdom, which can be regarded as polar cases with respect to the relevant features of the wage-setting process. However, in many respects, we find surprisingly similar results for both countries. Thereby, this paper also adds to the literature by providing new insights on the degree to which results from previous single-country studies can possibly be generalized.
Keywords: H22; H25; J31; 330